Proximal Fibular Autograft Reconstruction after Resection Giant Cell Tumor Distal Fibula - Mujaddid Idulhaq; Muhammad Luthfi Azizi (Universitas Airlangga, 2021)
Background: Giant cell tumor (GCT) is a destructive bone tumor. The predilection of the GCT is mostly on the epiphysial of long bones. GCT of the distal fibula is a very rare case that becomes challenging in surgical management. The chosen surgical management is crucial and still under debate.Case Report: A 38-years-old male complaint of a painful lump in the lateral side of his left ankle for three months. Plain radiographs demonstrate a lytic lesion involving distal fibula, appropriate with 2nd-grade Campanacci. MRI showed a mass centered on the distal fibula with intermediate to high T2 signal, low T1 signal, and homogenous contrast enhancement. The patient underwent a wide excision and reconstruction of the distal fibula with a fibular head graft from the ipsilateral side. After fifteen months of evaluation, the result was excellent. The patient can full-weight-bearing with a full range of ankle joint movement, return to daily activities without pain, and no signs of recurrence. Functional status measured by the MSTS and CAIT showed good results, with total scores was 28 and 27.Discussion: Ten centimeters distal fibula is a crucial component to form stability of the ankle. Reconstruction of the distal fibula after wide excision requires the bone graft and is considered to maintain ankle stability. It can be achieved using autograft from fibula or iliac crest.Conclusion: Reconstruction of distal fibula GCT with proximal fibular autograft showed a great result. This method is a viable option as it provides good pain relief and functional improvement.